2022
DOI: 10.1021/acs.inorgchem.2c02057
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Coordination of the Bis(amino-oxazoline) Ligand in Rare-Earth Metal Complexes: Synthesis, Structure, and Their Reactivity and Polymerization Performance

Abstract: Mononuclear rare-earth metal alkyl complexes supported by tetradentate dianionic bis(amino-oxazoline) ligands have been synthesized, and their reactivity toward small molecules and catalytic performance on ring-opening polymerization have been studied. Treatment of Ln(CH2SiMe3)3(THF)2 (Ln = Sc, Y; THF = tetrahydrofuran) with the bis(amino-oxazoline) proligand H2L afforded the corresponding rare-earth metal monoalkyl complexes L-Ln(CH2SiMe3)(THF) x (Ln = Sc, x = 0 (1); Ln = Y, x = 1 (2)). The isopropyl-substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…More than 92% yield could be achieved in 5 min in all cases when tetrahydrofuran was used as a solvent (Table , Entry 6–10) and the P r values of the resultant PLAs ranged from 0.68 to 0.77. These results showed that the yttrium complexes were among the most efficient rare-earth metal catalysts for the ROP of rac -LA. The comparative catalytic activity and heteroselectivity for all the yttrium complexes indicated the slight influence of chiral substituents, whatever their steric hindrance and electronic effect. All the scandium and lutetium complexes also promoted the ROP of rac -LA efficiently, producing the heteroselective PLAs ( P r = 0.61–0.71) with high molecular weight and narrow molecular weight distribution.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…More than 92% yield could be achieved in 5 min in all cases when tetrahydrofuran was used as a solvent (Table , Entry 6–10) and the P r values of the resultant PLAs ranged from 0.68 to 0.77. These results showed that the yttrium complexes were among the most efficient rare-earth metal catalysts for the ROP of rac -LA. The comparative catalytic activity and heteroselectivity for all the yttrium complexes indicated the slight influence of chiral substituents, whatever their steric hindrance and electronic effect. All the scandium and lutetium complexes also promoted the ROP of rac -LA efficiently, producing the heteroselective PLAs ( P r = 0.61–0.71) with high molecular weight and narrow molecular weight distribution.…”
Section: Resultsmentioning
confidence: 85%
“…The structure of PLAs strongly determined their physical properties and their subsequent applications. Hence, the catalytic systems based on different metal centers, such as Al, Zn, Mg, Zr, and rare-earth (Ln) metals, have been reported in the past decades, which could efficiently catalyze the polymerization of rac -LA and produce PLAs with diverse microstructures and physical properties. Particularly, rare-earth metal-based catalytic systems are among the ones that have attracted extensive research, due to their facility to enhance the catalytic activity and stereoselectivity .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that oxazoline-containing ligands have rich chemical properties for coordination with late transition metals, but their coordination with early transition metals, particularly rare-earth metals, has been relatively unexplored. Rare-earth metal complexes with bidentate, tridentate, or tetradentate oxazoline-based ligands were reported as efficient catalyst precursors for the hydroamination, ring-opening polymerization of rac -LA, and related lactone monomers, as well as the polymerization of olefin and 1,3-dienes (Figure a,b). ,, Recently, our group has also reported that the unsymmetrical diarylamido-oxazoline-based rare-earth metal complexes promoted the polymerization of 1,3-dienes with special catalytic performances, such as the unparallel stereoselective (co)­polymerization of isoprene and butadiene catalyzed by single rare-earth metal cationic species. , All of the previous works highlighted the special role of the oxazoline moiety in constructing ancillary ligands and regulating the steric and electronic effects of rare-earth metal complexes. As a part of our purpose in further searching for rare-earth metal catalysts for high cis -1,4-selective isoprene polymerization, we envisaged that the rare-earth metal complexes bearing oxazoline-based ligands, so-called enamino-oxazolinate ligands, could also exhibit specific catalytic performance in isoprene polymerization .…”
Section: Introductionmentioning
confidence: 99%